Diccionario crítico de la literatura mexicana (1955-2011) - Domínguez Michael, Christopher, 1962- (Letras mexicanas., 2013)
This book is both a personal anthology and a highly subjective and unscientific reference work, marrying the often acerbic, always poetic reviews and essays written on Mexican literature by the author over the past thirty years to the quixotic ideal of a comprehensive dictionary of Mexico's recent literary history. With well over 150 entries, it both introduces and interrogates the work of novelists, poets, essayists, and journalists working in Mexico between 1955 (date of the publication of Juan Rulfo's watershed Mexican Revolution novel Pedro Páramo) and the present day.